Lateral quadratus lumborum block versus transversus abdominis plane block for perioperative analgesia in patients undergoing laparoscopic colorectal cancer surgery: a randomized, controlled clinical trial - He Bai; Shuting Zhong; Xiaomei Yang; Lili Hou; Qianqian Liu; Yanan Wang; Zhou Wang; Baozhu Sun (BMC Anesthesiology)
Abstract Background Lateral quadratus lumborum block (QLB) and transversus abdominis plane block (TAPB) have been widely used in abdominal surgeries. This study aimed to compare the intraoperative analgesic effect, hemodynamic changes and postoperative complications of the two blocks in patients undergoing laparoscopic colorectal cancer surgery. Methods This was a randomized controlled trial that enrolled 189 patients scheduled for laparoscopic colorectal cancer surgery. Patients were randomly allocated into three groups: the QL group (n = 63) received bilateral ultrasound-guided lateral QLB; the TAP group (n = 63) received bilateral ultrasound-guided TAP block; and the GA group (n = 63) received no blocks. The primary outcome was cumulative remifentanil administration during laparoscopic colorectal cancer surgeries. Secondary outcomes included intraoperative hemodynamics (mean arterial pressure and heart rate), postoperative pain intensity, length of hospital stay and postoperative complications. Results One hundred eighty-four patients were eventually enrolled in the study. Intraoperative remifentanil administration was significantly lower in the QL group (398.69 ± 169.07 µg) than the TAP group (477.25 ± 156.55 µg) and the GA group (493.25 ± 195.32 µg) (P < 0.05), and there was no significant difference between the TAP group and the GA group (P > 0.05). At pneumoperitoneum establishment and abdominal incision time point, the MAP values of the GA group (98.59 ± 14.18 mmHg and 87.57 ± 12.03 mmHg, respectively) were significantly higher than in the TAP group and the QL group (91.18 ± 15.61 mmHg; 92.30 ± 11.91 mmHg and 80.95 ± 12.06 mmHg; 82.49 ± 10.99 mmHg, respectively) (P < 0.05). VAS scores at 15 min and 6 h after surgery were significantly lower in the QL group and the TAP group than in the GA group (P < 0.05). Conclusions In patients undergoing laparoscopic colorectal cancer surgery, the lateral QL block was superior than the TAP block in reducing intraoperative remifentanil usage. However, both blocks could provide greater intraoperative hemodynamic stability and better perioperative analgesia.